Analysis of Factors Associated with Preconception Nutritional Readiness Among Women of Reproductive Age in Kerinci Regency - Sintia, Ela; Desmawati, Desmawati; Nurhajjah, Siti (Newinera Publisher, 2025)
Women of Reproductive Age (WRA) as prospective mothers are a vulnerable group whose health status, particularly nutritional status, requires attention. The quality of future generations is determined by the mother's condition before pregnancy, as malnutrition during the preconception period can lead to both maternal and fetal malnutrition. This study aims to analyze the factors associated with preconceptions of nutritional readiness among WRA in Kerinci Regency. The study uses an analytical design with a cross-sectional approach. It was conducted at 5 Religious Affairs Offices in Kerinci Regency (The Office of Religious Affairs of East Air Hangat, Depati Tujuh, Sitinjau Laut, Danau Kerinci, and Keliling Danau) from 1 November to 30 November 2023. The sample consisted of 80 pre-marriage WRA registrants. Data were collected using questionnaires and analyzed using Chi-Square tests and Multiple Logistic Regression. The results showed significant associations between age (p-value 0.645), attitudes (p-value 0.005), occupation (p-value 0.006), physical activity (p-value 0.449), lifestyle (p-value 0.001), income (p-value 0.002), culture (p-value 0.018), food access (p-value 0.004), and the role of health workers (p-value 0.015) with preconceptional nutritional readiness. Multivariate analysis indicated that the most dominant factor was lifestyle, with an odds ratio (OR) of 17.75. In conclusion, the study found significant associations between various factors and preconceptions of nutritional readiness, with lifestyle being the most influential. Cross-sectoral cooperation and education are needed to intervene during the preconception period to prepare women for a healthy pregnancy and a positive pregnancy outcome.